ANALISIS DETERMINASI PERTUMBUHAN EKONOMI PROVINSI JAMBI - Ali Fahmi (Universitas Batanghari Jambi, 2018)
This research aims to analyze the effect of government spending, investment of foreign capital investment, capital investment In Land and labor against growth of Jambi province during the 2004-2015. This research using Time Series data with regression analysis